Development of Interactive Multimedia Indonesian Language Teaching Material Based on Problem-Based Learning (PBL) in Elementary Schools - Fitra Ramadani; Desyandri Desyandri; Elfia Sukma; Yeni Erita (AL-ISHLAH: Jurnal Pendidikan, 2024)
Contemporary education necessitates innovative teaching strategies and the integration of digital technologies. Current observations indicate that the learning process remains one-way, lacking student engagement. Thus, there is a pressing need for technological advancements in learning media, mainly Indonesian language instruction. This research endeavours to develop interactive multimedia teaching materials based on the Problem-Based Learning approach, utilizing the Articulate Storyline 3 application in combination with Google Forms for elementary schools. Following the ADDIE development model, the research employs various data collection methods, including observation sheets, validation instruments, interview questionnaires, practicality assessments, open evaluation questionnaires, and evaluation tests (Pretest and Posttest), which are then analyzed descriptively, qualitatively, and quantitatively. This research was conducted in 3 elementary schools in Padang City. The product validity test results obtained an overall average score of 95.38 in the very valid category. The results of the practicality test for teacher and student responses received an average score of 92.05 and 96.59 in the very practical category. The effectiveness test results are effective, with an average N-Gain Score of 0.81. This interactive multimedia meets the characteristics of interesting learning multimedia, is easy to operate, and is very suitable for meeting students' needs.